ENGLISH TEACHERSÃ¢â¬â¢ PERCEPTIONS ABOUT THEIR TEACHING: USING ACTIVITY THEORY TO IDENTIFY CONTRADICTIONS - Ardi Marwan (TEFLIN, 2009)
Abstract: This paper highlights the findings of a study which was undertaken at a vocational higher institution in Indonesia. The aim of the study was to explore English teachersÃ¢â¬â¢ perceptions about their English language teaching (ELT) in this institution. Activity theory (AT) was employed as the framework for guiding the study owing to the fact that its focus was on the identification of contradictions occurring in the activity system. From AT analysis, several contradictions could be located within the context of ELT in this institution. Recommendations for the improvement of ELT in this particular institution were also provided.